2016
DOI: 10.17511/ijpr.2016.i06.07
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of ascites in children at tertiary care hospital, North Karnataka

Abstract: Introduction: Ascites is a common clinical problem in children with liver and renal disease. The peripheral arterial vasodilation hypothesis is mostly accepted as the patho-physiological basis of ascites. The most important complication is spontaneous ascitic fluid infection in the form of spontaneous bacterial peritonitis (SBP) and its variants. Objective: To know the incidence, etiology, associated clinical co-morbidities & the outcome (morbidity & mortality) of the hospitalized children with ascites. Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…Females have around 20 ml of abdominal fluid, which may indicate that females are more likely to have ascites than males [9]. The majority of the affected patients in the study were found to be males, similar to the findings of a previous study where the maximum number of the affected patients were males [10].…”
Section: Resultssupporting
confidence: 84%
“…Females have around 20 ml of abdominal fluid, which may indicate that females are more likely to have ascites than males [9]. The majority of the affected patients in the study were found to be males, similar to the findings of a previous study where the maximum number of the affected patients were males [10].…”
Section: Resultssupporting
confidence: 84%
“…There are various theories that have been proposed for the formation of ascites [10], which include the following:…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted at Nijalinagappa Medical College, 13 Bagalkot, on 102 children over a period of 18 months, nephrotic syndrome contributed 32.35% followed by abdominal tuberculosis 8.80% and chronic liver diseases about 8.80%.…”
Section: Discussionmentioning
confidence: 99%